Supramolecular free radicals: near-infrared organic materials with enhanced photothermal conversion1. Issue 7 (15th July 2015) - Jiao, Yang; Liu, Kai; Wang, Guangtong; Wang, Yapei; Zhang, Xi
<x xml:space="preserve">Abstract</x> A novel kind of supramolecular free radical with significantly improved free radical yield and enhanced near-infrared photothermal conversion has been fabricated.